Zoledronic acid‐induced oxidative damage and endoplasmic reticulum stress‐mediated apoptosis in human embryonic kidney (HEK‐293) cells. Issue 8 (19th May 2022) - Kara, Mehtap; Boran, Tuğçe; Öztaş, Ezgi; Jannuzzi, Ayse Tarbin; Özden, Sibel; Özhan, Gül
Abstract: Zoledronic acid, a nitrogen‐containing bisphosphonate drug, is used for the treatment of osteoporosis, Paget's disease of bone, and tumor‐induced osteolysis. Zoledronic acid has also gained a place in cancer treatment due to its cytotoxic and antiproliferative effects in many cancer cells. Although zoledronic acid is considered safe, kidney damage is still one of the concerns in therapeutic doses. In the study, the aim was to assess the nephrotoxic profiles of zoledronic acid in the human embryonic kidney (HEK‐293) cells. Cytotoxicity evaluation was performed by 3‐[4, 5‐dimethylthiazol‐2‐yl]−2, 5‐diphenyl‐tetrazolium bromide (MTT) and neutral red uptake tests, while oxidative stress was performed by reactive oxygen species (ROS) production via flow cytometry, and the incomprehensible evaluation of ROS‐related genes by RT‐PCR and apoptosis was performed with Annexin‐PI analysis in flow cytometry. The obtained result showed that zoledronic acid inhibited cell viability (IC50 values were determined as 273.16  by MTT) and cell proliferation in a concentration‐dependent manner, induced ROS production, caused glutathione depletion, and increased oxidative stress index and endoplasmic reticulum (ER) stress, indicating severe cellular stress. The expression levels of oxidative damage ( L‐fabp, α‐GST, Nrf2, and HMOX1 ), ER stress ( CASP4, IRE1‐α, GADD153, and GRP78 ), and apoptosis ( Bcl‐2, Bax, Cyt‐c, p53, CASP9, CASP3, NF‐κB, TNF‐α, and JNK ) related genes were altered as well as IRE1‐α protein levels. Herein, we were the first to show that increased oxidative stress and ER stress resulting in apoptosis are the key molecular pathways in zoledronic acid‐induced nephrotoxicity equivalent to clinically administered concentrations.